Effect of clomipramine on monoamine metabolites in the cerebrospinal fluid of behaviorally normal dogs. - Hewson, C J (2000)
The tricyclic antidepressant, clomipramine, is an effective treatment for canine compulsive disorder (canine CD). This disorder is a clinical syndrome of abnormal conflict behaviors and its pathophysiology is unknown. However, because clomipramine is an effective treatment, information about the drug's neurochemical effect could enhance the understanding of canine CD. The following experiment used 6 behaviorally normal dogs to assess the effect of clomipramine (3 mg/kg, q24h, PO) on the central turnover of 3 monoamines (serotonin, dopamine, and norepinephrine) as measured by the concentrations of their respective metabolites in cerebrospinal fluid (CSF). In a randomized, placebo-controlled, AB-BA crossover experiment, cisternal CSF was taken after 1, 2, 4, and 6 wk on each treatment. No effect of clomipramine was detected. This contrasts with human studies that have suggested that clomipramine affects the concentrations of monoamine metabolites in lumbar CSF. However, those papers do not address methodological assumptions, such as (i) metabolites in CSF originate only from the brain, and (ii) concentrations of metabolites in cisternal/lumbar CSF reflect the concentrations in local areas of the brain. Notwithstanding the small sample size, our results suggest that more localized sampling techniques (e.g. microdialysis) are needed when examining the effect of drugs on central monoamine metabolites. Clomipramine's efficacy for canine CD indicates the need for neurobiological research and, to our knowledge, our study is the first of its kind in dogs. The resulting data are preliminary but they can inform optimal neurobiological studies of canine CD.